Challenges facing the physician in the 21st century - Emery, H. (2000)
Notes that one dilemma facing the physician of the 21st century is the need to recognize his/her changing role and to integrate his/her traditional clinical skills with the social intervention (including spirituality) needed to achieve total patient care. Suggests that the issues of primary health care, poverty, pollution, health insurance ,the cost of health care, and alternative medicine, ethical and moral dilemmas, represent some of the major challenges. Indicates that the challenge to the doctor is that he/she must always adopt positions which are ethically, morally and legally sound.